MANAJEMEN PEMBERDAYAAN KADER DALAM PENGELOLAAN POSYANDU DI KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT - , Putrawangsa ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Community empowerment is one of health program which involving several institution, in the regional government since the regional autonomy and decentralization been applied form of great opportunity for the regional government and their agencies to perform development according to the peopleâs need in the region. Community or public empowerment is entrance gate to get basic health services for the public with public participation as major actors. Objectives: To understanding the implementation in empowerment the cadres of the integrated services station which be performed and be developed by the Health Office and related agencies in managing the cadres empowerment in Central Lombok Regency. Methods: This was a descriptive study using qualitative methods. The research variables were the authority of Health Office and related agencies in performing an empowerment of cadres of integrated services station. The informants were selected by non probability approach using purposive technique. Data were collected by indepth interview, observation, documents study, and analysis of secondary data. The study was using emik-etik perspective. Their scientific basic is using analysis by inductive approach. Results: The empowerment which be performed without considering a condition and the need of the public, would not able to accomplishing the empowerment of integrated services station cadres, resulted in the involved institutions, agencies and offices in the empowerment without a good coordination. In 2009, there were active cadres in integrated services station activity of 4,887 or 72%, not active cadres 1,835 or 28%. There were difference programs implementation in each sectors related to empowerment, there were no policy yet in fund management which originated from public, privates, and non government organization participation. Conclusion: The coordination in cadre empowerment of integrated services station, between BPMD, BPPK, DINKES, not going on. There were no policy on equal allocation in ADD for integrated services station. In managing the gardens of an integrated services station, need to pay attention to increasing a public participation.